The brazilian territorial formation in geography textbooks: in pursuit of a decolonial analysis - Loback, Victor; Bezerra, Amélia Cristina Alves (Geografares, 2018)
In this paper, we pursue to verify how Coloniality of Knowledge engenders the scholar Geography, mainly about Brazilian territorial formation. For this, we start presenting a brief theoterical reflection about the decolonial thought and the scholar curriculum; then, we discuss narratives in textbooks about this theme; after we bring the report of five Geography teachers of public schools in Rio de Janeiro to comprehend how they handle with the approaches contained in textbooks; we conclude setting challenges to construct an decolonial teaching.
Keywords: Geography Teaching; Coloniality of Knowledge; Textbooks